Comparative Study of the NOx, CO Emissions, and Stabilization Characteristics of H2-Enriched Liquefied Petroleum Gas in a Swirl Burner - Abay Mukhamediyarovich Dostiyarov; Dias Raybekovich Umyshev; Zhanar Abdeshevna Aidymbayeva; Ayaulym Konusbekovna Yamanbekova; Zhansaya Serikkyzy Duisenbek; Madina Bakytzhanovna Kumargazina; Nurlan Rezhepbayevich Kartjanov; Ainur Serikbayevna Begimbetova (Energies)
The global shift toward renewable fuels and the reduction in anthropogenic environmental impact have become increasingly critical. However, the current challenges in fully transitioning to environmentally friendly fuels necessitate the use of transitional fuel mixtures. While many alternatives have been explored, the combination of hydrogen and LPG appears to be the most practical under the conditions specific to Kazakhstan. This study presents experimental findings on a novel burner system that utilizes the airflow swirl and hydrogen enrichment of LPG. It evaluates the effects of hydrogen addition, fuel supply methods, and swirl intensity—achieved by adjusting the outlet vanes—on flame stabilization as well as NOx and CO emissions. The results show that the minimum NOx concentration achieved was 12.08 ppm, while the minimum CO concentration was 101 ppm. Flame stabilization studies indicate that supplying the fuel at the center of the burner, rather than at the base, improves stabilization by 23%. Additionally, increasing the proportion of hydrogen positively affects stabilization. However, the analysis also reveals that, as the hydrogen content in the fuel rises, NOx concentrations increase. These findings highlight the importance of balancing the hydrogen enrichment, airflow swirl, and fuel supply methods to achieve optimal combustion performance. While hydrogen-enriched LPG offers enhanced flame stabilization, the associated rise in NOx emissions presents a challenge that requires careful management to maintain both efficiency and environmental compliance.